Evaluasi Kegiatan Surveilans dalam Pencegahan dan Pengendalian Infeksi di RSUD KRT. Setjonegoro Wonosobo - Mahardika Primadani (Universitas Ahmad Dahlan, 2019)
Nosocomial infections or currently known as Health care associated infections (HAIs) is an important problem worldwide and an interesting issue to research, especially regarding infection prevention efforts. The prevalence of HAIs in world hospitals reaches 9% or approximately 1.40 million. From the surveillance data of Setjonegoro Hospital from 2018 to 2020, it was found that the incidence of phlebitis was 7.2 ‰. One of the strategies to control HAIs is surveillance. The purpose of this study was to evaluate the implementation of the surveillance program in the Prevention and Control of Infection at RSUD Setjonegoro, Wonosobo Regency. This type of research is a qualitative study with a phenomenological design. The research subjects were the chair of the PPI, IPCN, IPCLN and IPCD committees. The instruments used were observation and interview guidelines. The data analysis technique used the theory of Miles and Huberman. Surveillance activity in RSUD KRT. Setjonegoro Wonosobo is quite optimal, both in terms of human resources, facilities, and infrastructure to the timeliness of reporting, so that the surveillance reports always get feedback to find out what follow-up plans will be carried out. The mistake that often occurs is the negligence of officers in inputting surveillance data. The surveillance activities at the Setjonegoro Regional Hospital have been running well, all PPI Teams have received training related to surveillance activities, data input is carried out using software, reporting of surveillance results is running on time, and feedback is given both verbally and in writing.